Kemampuan literasi remaja wanita di Desa Tawangrejo Kabupaten Blitar dalam menghadapi budaya fashion pada era teknologi informasi - Arin Prajawinanti; Ria Fitria (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. The more information a person needs, the more active the person is in searching for information. Adolescents tend to follow fashion updates because of, their curiosity. This study aims to identify the triggers for youth information needs for fashion. Data Collection Methods. The paper used a qualitative approach with descriptive methods. Data Analysis. Data analysis was carried out first by reducing the data obtained through observations, interviews, and literature study. Results and Discussion. There are five factors that encourage the process of information seeking behavior in adolescents, psychological conditions, demographics, interpersonal relationships, environment, and characteristics of information. Information seeking behavior by youth accidentally tend to create further interests. Several obstacles appeared in search fing information, these include difficulties to find relevant information, lack of satisfaction in model of clothes, and hard to find information . However, these obstacles can be overcome by digging information through other sources and conducting searches immediately after the needs. Conclusion. The trigger for the information needs of adolescents related to fashion is the need to support their appearance. Many adolescents see fashion a value system in the society.